2007
DOI: 10.1016/j.tetlet.2007.01.034
|View full text |Cite
|
Sign up to set email alerts
|

Toward the total synthesis of Scleritodermin A: preparation of the C1–N15 fragment

Abstract: The synthesis of the C 1 -N 15 fragment of the marine natural product Scleritodermin A has been accomplished through a short and stereocontrolled sequence. Highlights of this route include the synthesis of the novel ACT fragment and the formation of the α-keto amide linkage by the use of a highly activated α, β-ketonitrile. KeywordsScleritodermin A; thiazole; α-ketoamide; Wittig Marine sponges of the order Lithistida are excellent sources of bioactive metabolites. 1 They produce cyclic peptides with non-protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
2

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 27 publications
0
18
0
2
Order By: Relevance
“…Синтез блока (4S-119) из L-алло-изолейцина (122) включал взаимодействие (после защиты аминогруппы) с илидом из PPh 3 =CHCN, [69] озонолиз соединения 123 по методу Вассермана [70] и взаимодействие с HN 3 по Мицунобу [71] (Схема 32). Синтетический блок (4R-119) синтезирован из другого изомера 122.…”
Section: синтез противоракового агента склеритодермина аunclassified
See 1 more Smart Citation
“…Синтез блока (4S-119) из L-алло-изолейцина (122) включал взаимодействие (после защиты аминогруппы) с илидом из PPh 3 =CHCN, [69] озонолиз соединения 123 по методу Вассермана [70] и взаимодействие с HN 3 по Мицунобу [71] (Схема 32). Синтетический блок (4R-119) синтезирован из другого изомера 122.…”
Section: синтез противоракового агента склеритодермина аunclassified
“…Сложноэфирная функция в полученном тиазоле 126 переведена в карбонильную, [67] и соединение 127 вовлечено в реакцию олефинирования по Виттигу, приводящую исключительно к E-ненасыщенному альдегиду 128. Олефинирование последнего в условиях реакции Хорнера-Эммонса в модификации Стилла-Дженари [69] позволило построить (2Z,4Е)-сопряженную систему синтона (2Z-120), а олефинирование по Хорнеру-Уодсворту-Эммонсу [68] получить (2E,4Е)-олефин (2E-120) (Схема 33).…”
Section: синтез противоракового агента склеритодермина аunclassified
“…The synthesis of these fragments was based on the methodology previously described by us for the synthesis of ACT fragment. 9 Firstly, we obtained thiazole 4 and oxazole 5 by cyclodehydration of a b-hydroxyamide or thioamide derived from Lserine and L-tyrosine (Scheme 2). The thiolysis of oxazoline 7 in H 2 S/MeOH is high-yielding, and offers an alternative to the thionation of peptides using Lawesson's reagent.…”
Section: Chemistrymentioning
confidence: 99%
“…In 2007, our group reported the preparation of the C 1 eN 15 fragment, 9 and recently, Nan et al reported the total synthesis of the originally proposed and revised structures of scleritodermin A, 1 and 2, Figure 1. 10 The present studies allowed us to obtain different key fragments that have been tested for cytotoxic and antihelminthic activity.…”
Section: Introductionmentioning
confidence: 99%
“…As a part of our search for anticancer or antiparasitic drugs candidates employing molecular simplification [17][18][19][20][21][22], we focused on the synthesis of 2,4'-biheterocycles as scaffolds of bioactive products using Hantzsch and cyclodehydration-oxidation reactions. In the present work, we report the synthesis of biheterocycles of type 1 (Scheme 1) using commercially available starting materials: L-serine methyl ester hydrochloride, ethyl bromopyruvate, and thioacetamide.…”
mentioning
confidence: 99%